1968
DOI: 10.1103/physrevlett.21.1849
|View full text |Cite
|
Sign up to set email alerts
|

Double-Pole Fit toA2(1300)Mass Spectra

Abstract: A double-pole explanation of the A2(1300) meson is shown to be consistent with recent bubble-chamber measurements of its missing-mass spectrum and of its Xi^iCi^-decaymode mass spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A second possibility is that the mass matrix itself has isospin dependence that has not yet been exploited. A third, rather remote, possibility is that the A2 system is formed with three strongly coupled mesons, the third meson now coupling only to KK the same way as mg does in the earlier analyses (13,14). The first method seems most likely, however, as an analogous effect occurs in the nit decay channel of the p° and u mesons.…”
Section: Fits To Previous Datamentioning
confidence: 87%
See 1 more Smart Citation
“…A second possibility is that the mass matrix itself has isospin dependence that has not yet been exploited. A third, rather remote, possibility is that the A2 system is formed with three strongly coupled mesons, the third meson now coupling only to KK the same way as mg does in the earlier analyses (13,14). The first method seems most likely, however, as an analogous effect occurs in the nit decay channel of the p° and u mesons.…”
Section: Fits To Previous Datamentioning
confidence: 87%
“…The single-barrier potential of interest is V(r) = V^ô(r -a), a > 0, (13) with the convenient choice of a = 1 to set the scale of the interaction. The Jost solutions for this potential are…”
Section: Resonances Of a Two-barrier Potential Problemmentioning
confidence: 99%
“…A Model of the A2 Meson found that the model with the 6^ (hereafter written 6^) range 0.08 < 6^ < 1.25 fitted the data of References 7 and 9 quite 2 well, the indicated limits having X probabilities of 10%, the best fits (near 6^ = 0.70) having 90% probabilities (13).…”
Section: (16)mentioning
confidence: 99%
“…The single-barrier potential of interest is V(r) = V^ô(r -a), a > 0, (13) with the convenient choice of a = 1 to set the scale of the interaction. The Jost solutions for this potential are 0^(k,r) = k""^"^[u^(kr) + ©(r -l)V^u^(k)g^(k,r,l) ] (14) and f^(k,r) = w,(kr) -0(1 -r)V^w^(k)g^ (k,r, 1) ,…”
mentioning
confidence: 99%